Doprowadź do najprostszej postaci:

(4x-2y+3)-( 6x-4y-3)-(-2x-7y+8)=

4x(-2x-3y+5)=

-3x(2x-4)-8x(3x-5)=

(4x-3)(-2x-5)+ 4x(2x-4)=

(2x-1)(3x-2)-(3x-4)(4x-1)=



Odpowiedź :

Odpowiedź:

1.

[tex] =4x - 2y + 3 - 6x + 4y + 3 + 2x + 7y - 8 = 9y - 2[/tex]

2.

[tex] = - 8 {x}^{2} - 12xy + 20x[/tex]

3.

[tex] = { - 6x}^{2} + 12x - 24 {x}^{2} + 40x = - 30 {x}^{2} + 52x[/tex]

4.

[tex] = - 8 {x}^{2} - 20x + 6x + 15 + {8x}^{2} - 16x = - 30x + 15[/tex]

5.

[tex] {6x}^{2} - 4x - 3x + 2 - {12x}^{2} + 3x + 16x - 4 = - 6 {x}^{2} 12x - 2[/tex]